Social Media Use, Religiosity and Perceived Social Support Predicting Mental Health - IBINI, Olabode; AKPURU, Emmanuel; ATOBA, Zynat; UYE, Emmanuel (Jurnal Ekonomi, Manajemen, Ilmu Sosial dan Politik, 2025)
This research aims at investigating the predictive ability of social media use, religiosity and social support on mental health among undergraduate samples in Nigeria. Cross-sectional survey design was adopted while purposive sampling technique was used to select the study population. Data were collected from 401 undergraduates using validated questionnaires and analyzed using hierarchical   multiple regression to test one hypothesis which was accepted at p <.001 level of significance. The result revealed that social media use, religiosity and social support jointly predicted mental health among study participants [R2 = .31, F (3, 398) = 28.952, p <.001). Furthermore the result showed that social media use (β =.193, p <.001) and religiosity (β = .45, p <.001) independently predicted mental health among study participants. The study concluded that social media use, religiosity and social support are strong predictors of mental health among undergraduate samples. It is recommended that the university authority should sensitize the students on the proper use of social media while the parents and other stakeholders should provide social support to the students to reduce any negative effects on their mental health.